Photoacclimatization by the coral Montastraea cavernosa in the mesophotic zone: light, food, and genetics - Michael P. Lesser; Marc Slattery; Michael Stat; Michiko Ojimi; Ruth D. Gates; Andrea Grottoli (Ecology, 2010)
Most studies on coral reefs have focused on shallow reef ( Montastraea cavernosa has a wide depth distribution, and it is one of the most numerous corals at mesophotic depths. Using a range of optical, physiological, and biochemical approaches, the relative dependence on autotrophy vs. heterotrophy was assessed for this coral from 3 to 91 m. These measurements show that the quantum yield of PSII fluorescence increases significantly with depth for M. cavernosa while gross primary productivity decreases with depth. Both morphological and physiological photoacclimatization occurs to a depth of 91 m, and stable isotope data of the host tissues, symbionts, and skeleton reveal a marked decrease in productivity and a sharp transition to heterotrophy between 45 and 61 m. Below these depths, significant changes in the genetic composition of the zooxanthellae community, including genotypes not previously observed, occur and suggest that there is strong selection for zooxanthellae that are suited for survival in the light‐limited environment where mesophotic M. cavernosa are occurring.